Inside third world cities - Lowder, Stella (London, 1986)
The problems faced by Third World city populations are truly enormous. Competition for goods and services is ever increasing as city expansion outstrips public and private investment. Access to these is filtered not merely by purchase power but by structures which are shaped by inheri patterns and practices and by the city's contemporary links with the world capitalist system. These procedures, distributive systems and social conventions reflect the complex histories of the cities, most of which have been subject to colonial rule and of their inhabitants, many of whom are either migrants or first generation citizens. These structures are revealed in such activities as administration, public services, planning, construction, housing finance and retailing and in the spatial structure of the cities. The book considers cities throughout the Third World and compares examples from different continents in each chapter.
Keywords: Cities and towns Developing countries